Pengembangan Media Pembelajaran Mind Mapping Berbantuan Gambar untuk Meningkatkan Keterampilan Menulis Teks Deskripsi pada Pelajaran Bahasa Indonesia Kelas IV Madrasah Ibtidaiyah - Suriyani; Abdul Muktadir; Agus Susanta (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to develop: image-assisted mind mapping learning media based on problem based learning to improve the ability to write descriptive text. The research was conducted at MIN 2 Bengkulu Tengah in class IV. This research is development research (Research and Development) with the ADDIE model. The instruments used were feasibility test questionnaires and student response questionnaires and teacher interview guidelines. Data analysis is used to determine the validity of the media using cross tabulation and distribution of questionnaires for student responses and interviews for teacher responses in using mind mapping media. percentage technique and processed descriptively. The results of the mind mapping media feasibility test by the validator were reviewed from the material, language and presentation aspects, the material feasibility was 0.70 (feasible criteria), the language feasibility results were 0.90 (feasible criteria) and the display feasibility results were 0.80 (very feasible criteria). The results of the field test of mind mapping media by conducting posttests and pretest with the gain test results showing 20 students with a high gain criterion of 5 students with a percentage of 25% then medium criteria of 15 students with a percentage of 75%. Apart from that, the results of interviews with class IV teachers showed a positive response. In other words, the mind mapping media used is beneficial and effective for use as a learning medium in improving students' descriptive text writing skills.